2007
DOI: 10.1016/j.febslet.2007.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Main antimicrobial components of Tinospora capillipes, and their mode of action against Staphylococcus aureus

Abstract: In this investigation, the antibacterial modes of action of Radix Tinosporae, its major single components, and nine antibiotics with different targets or modes-of-action on Staphylococcus aureus were studied. Metabolic profiles of cultures treated with different medicines were acquired by HPLC/ESI-MS. After HPLC-MS data pretreatment, those profiles acquired were reduced into several MS vectors. Then statistical processing by principal components analysis was carried out upon those vectors, two conclusions coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…In independent experiments, peptidyl-transferase was confirmed as the molecular target of TAN 1057 A/B, a natural compound structurally related to Bay 50-2369 (13). Metabolomic profiling is based on comprehensive analysis of global metabolism and has been enabled by recent technological advances in the quantification of cellular metabolites (2,7,14). Yu et al (14) investigated the mechanism of action of Radix Tinosporae extract by comparing the metabolomic profile of treated Staphylococcus aureus to profiles induced by nine antibiotics with known mechanisms of action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In independent experiments, peptidyl-transferase was confirmed as the molecular target of TAN 1057 A/B, a natural compound structurally related to Bay 50-2369 (13). Metabolomic profiling is based on comprehensive analysis of global metabolism and has been enabled by recent technological advances in the quantification of cellular metabolites (2,7,14). Yu et al (14) investigated the mechanism of action of Radix Tinosporae extract by comparing the metabolomic profile of treated Staphylococcus aureus to profiles induced by nine antibiotics with known mechanisms of action.…”
mentioning
confidence: 99%
“…Yu et al (14) investigated the mechanism of action of Radix Tinosporae extract by comparing the metabolomic profile of treated Staphylococcus aureus to profiles induced by nine antibiotics with known mechanisms of action. Principal component analysis (PCA) of metabolomic profiles, obtained using high-performance liquid chromatography-mass spectrometry (HPLC-MS) data, revealed that the mechanism of action of Radix Tinosporae was similar to that of rifampin and norfloxacin (14). Techniques for multiparameter imaging-based phenotypic profiling rely on high-throughput fluorescence microscopy (15) or morphological analysis (16) and have shown great promise in drug discovery research (2,7).…”
mentioning
confidence: 99%
“…231 Gene expression profiling with either the entire transcriptome 232,233 or a subset of reporter genes 234,235 has also been used to predict modes of action for natural products. However, because these transcriptomic screens are still relatively costly, there is a great interest in applying metabolomics analyses to predict natural product modes of action using either natural product extracts 236 or purified compounds. 237-242 Vincent et al have recently shown untargeted metabolomics can effectively identify compound modes of action when specific metabolic pathways are the primary drug target.…”
Section: Investigations Of Secondary Metabolite Bioactivitymentioning
confidence: 99%
“…Jatrorrhizine is a kind of quaternary protoberberine alkaloids (QPA) and was considered as one of the active constituents of Coptis chinensis Franch [5,6]. Jatrorrhizine has multiple bioactivities, such as hypoglycemic [7], antimicrobial [8], and antioxidant activities [9]. In recent years, berberine derivatives with various heterocyclic rings, such as thiophene, pyrrole, piperidine, and carbazole, were demonstrated as both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%